2014
DOI: 10.1007/s00268-014-2572-5
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of Radical Antegrade Modular Pancreatosplenectomy for Adenocarcinoma of the Left Pancreas: Significance of En Bloc Resection Including the Anterior Renal Fascia

Abstract: BackgroundRadical antegrade modular pancreatosplenectomy (RAMPS) has theoretical advantages for curative resection of adenocarcinomas of the left pancreas. The anterior renal fascia is a key structure, and resection planes should run posterior to this fascia. However, it is difficult to delineate this fascia and set a precise dissection plane. We modified RAMPS to achieve such a precise dissection plane with ease.MethodsAfter clamping the splenic artery, the third duodenal portion was mobilized from the left t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The current survival results are probably very close to the true population results. Although there are a number of reports regarding survival in patients having RAMPS for adenocarcinoma , there are not yet other reports of 5‐year survival in 50 or more patients. Murakawa et al reported 3‐year survival of 38.6% in 49 patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current survival results are probably very close to the true population results. Although there are a number of reports regarding survival in patients having RAMPS for adenocarcinoma , there are not yet other reports of 5‐year survival in 50 or more patients. Murakawa et al reported 3‐year survival of 38.6% in 49 patients .…”
Section: Discussionmentioning
confidence: 99%
“…RAMPS is a right‐to‐left operation, whereas laparoscopic abdominal surgery seems best suited for inferior to superior dissection. Modifications described by Rosso et al and Kitagawa et al to facilitate exposure of the left renal vein in the open procedure may aid the laparoscopic approach. Laparoscopic anterior RAMPS seems to provide the usual benefits of laparoscopy and should be explored further especially in thin patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the advent of nab-paclitaxel (nab-PTX) plus gemcitabine (GEM) therapy (GnP therapy) and 5-FU, leucovorin, irinotecan and oxaliplatin (FOLFIRINOX) therapy improved treatment outcome of unresectable PDAC (3,4), surgery is the only method to achieve long-term survival. Curative (R0) resection comprising wide lymph node dissection and complete removal of the extrapancreatic nerve plexus of the superior mesenteric artery (SMA) or celiac axis (5)(6)(7)(8)(9)(10) has been shown to be one of the key factors influencing survival of patients with PDAC. However, even in patients who undergo resection, 5-year survival is poor at <30% and the prognosis of PDAC has not improved.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even in patients who undergo resection, the 5-year survival rate is poor at between 7 and 24%, whereas the median survival time is ~1 year in the majority of series, indicating that surgery alone is inadequate. A number of surgeons have attempted radical pancreatic resection, comprising wide lymphadenectomy and removal of the extrapancreatic nerve plexus, to improve outcomes (6)(7)(8)(9)(10). However, no improvement in the prognosis of pancreatic cancer has been achieved.…”
Section: Introductionmentioning
confidence: 99%